2016
DOI: 10.3892/mmr.2016.5613
|View full text |Cite
|
Sign up to set email alerts
|

FSH aggravates bone loss in ovariectomised rats with experimental periapical periodontitis

Abstract: Periapical bone loss is one of the prominent pathological and clinical features of periapical periodontitis. Previous studies have demonstrated that follicle-stimulating hormone (FSH) could directly affect skeletal remodelling by stimulating the formation and the function of osteoclasts in vitro and in vivo. However, the effect of FSH on periapical bone loss remained to be fully elucidated. In the current study, a rat model was established in order to verify the effect of FSH in experimental periapical lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Little is known about the expression of proinflammatory cytokines in the periapical lesion of ovariectomized animals. Previous studies have observed that the response to periapical lesion induction in ovariectomized rats was more intense, promoting increased gene expression (Romualdo et al 2018) or immunostaining (Qian et al 2016) of several proinflammatory cytokines, indicating that microbial infection combined with OVX plays an important role in the immunoinflammatory response in the periapical lesion. According to Yang et al (2015), the addition of ALN in osteoclast cell culture causes anti-inflammatory effects, inhibiting IL-1b, IL-6, PGE2 and TNF-a.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Little is known about the expression of proinflammatory cytokines in the periapical lesion of ovariectomized animals. Previous studies have observed that the response to periapical lesion induction in ovariectomized rats was more intense, promoting increased gene expression (Romualdo et al 2018) or immunostaining (Qian et al 2016) of several proinflammatory cytokines, indicating that microbial infection combined with OVX plays an important role in the immunoinflammatory response in the periapical lesion. According to Yang et al (2015), the addition of ALN in osteoclast cell culture causes anti-inflammatory effects, inhibiting IL-1b, IL-6, PGE2 and TNF-a.…”
Section: Discussionmentioning
confidence: 96%
“…) or immunostaining (Qian et al . ) of several proinflammatory cytokines, indicating that microbial infection combined with OVX plays an important role in the immunoinflammatory response in the periapical lesion. According to Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, only ovariectomy model was unable to highlight the roles of FSH. Our group administered FSH and its inhibitor based on OVX model to study the independent role of FSH 18,20 . No obvious changes were found in E2 levels of OVX groups after FSH and LE application.…”
Section: Discussionmentioning
confidence: 99%
“…Follicle-stimulating hormone (FSH) plays a role as a reproductive hormone. However, several studies have suggested the probable extragonadal effects of FSH on bone mass [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and body mass. [15,16] Traditionally, increased bone resorption during menopause has been attributed to reduced estrogen levels.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]6,8,17] Sun et al [1] reported that, irrespective of the nature or severity of estrogen deficiency, high FSH levels are prerequisites for hypogonadal bone loss. Multiple animal studies have demonstrated that FSH aggravates bone loss, [14,18] and that inhibiting FSH is osteoprotective. [19,20] Likewise in humans, the Study of Women's Health Across the Nation (SWAN) found a negative correlation between serum FSH levels and BMD in perimenopausal women.…”
Section: Introductionmentioning
confidence: 99%